PENGARUH EXPERIENTIAL MARKETING DAN BRAND TRUST TERHADAP KEPUASAN PELANGGAN DAN LOYALITAS PELANGGAN LABERSA GRAND HOTEL DAN CONVENTION CENTRE DI PEKANBARU - Taufik, Muhammad Teza; Rahayu, Deny Danar; ', Jushermi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research aimed to analysze Experiential Marketing and Brand Trust on Customer Satisfaction and Customer Loyalty. This research was conducted at the customer Labersa Grand Hotel and Convention Centre in the city of Pekanbaru. Where these customers should have more than one time stay at Hotel Labersa. In this study consists of four variables: two variables eksogen / independent variables and two variables endogen / dependent variables. These variables are Customer Loyalty (Y2), Customer Satisfaction (Y1), Brand Trust (X2), and Experiential Marketing (X1). This study was conducted using a sample of 100 people. This study using simple random sampling technique that is making members of the sample of the population was randomly without regard to strata that exist in this population. Thereby done when members of the population considered to be homogeneous. In terms of data analysis, this study using Path Analysis with SPSS (Statistical Package for Social Science) version 20. Based on the hypothesis tests conducted, results showed that Experiential Marketing Research and Brand Trust positive and significant impact on customer satisfaction. Experiential Marketing and Brand Trust also positive and significant impact on the Customer Loyalty, Customer Satisfaction positive and significant impact on the Customer Loyalty. And there is a positive and significant effect of the variable Experiential Marketing Customer Loyalty through Customer Satisfaction. And positive and significant influence between the variables of the Brand Trust Customer Loyalty through Customer Satisfaction.Keywords: Experiential Marketing, Brand Trust, Customer Satisfaction, Customer Loyalty.